Budgetary Process and Financial Performance of Embu County Government, Kenya - Ngaira, Erick (University of Embu, 2019)
The rate of absorbtion of development funds by Kenyan County Governments has been low, a factor that has gnawed at it for years since the inception of County Government in Kenya. The study ought to cletennine the effect of budgetary process on financial performance ofEmbu County government. The respondents consisted of 33 staff members from sectoral accountants, budget office, finance office, lFMIS department and County Economist. The study adopted descriptive research design where a questionnaire was used to collect data. The researcher also utilized County Fiscal Strategy Papers, County Government Budget Implementation Review Reports, County Budget Review and Outlook Papers and other vital Government Reports. The study applied descriptive and inferential statistics. Inferential statistics was applied for the purpose of determining the relationship between dependent variable and independent variables where a regression analysis was clone using Statistical Package for the Social Sciences (SPSS) version 25. The research findings were presented via pie chart, bar charts and frequency tables. The study established that though Public Financial Management Act had been effectively adopted by the County in its budgetary planning, the public had not been effectively involved in budgetary planning, In addition, the County Government had fully improved on uptake of development funds. The study concluded that the two components of budgetary process that is budgetary planning and, budgetary monitoring and evaluation were significant and had influence on financial performance of the County. The study recommended that the County Government should that the audit committee is well constituted and there is adequate staff in finance, budget office, accounting procurement departments to prevent erroneous financial reporting. Furthermore, the study recommended that the County Government should make implementation of development projects a priority in order to improve on absorbtion of development funds. The study recommend that further studies should be undertaken on: budgetary process and financial Performance of County Governments in Kenya, factors affecting absorbtion of development funds by County Goverrunents in Kenya and another study on effect of public participation on budgetary planning by County Governments in Kenya